Poor myocardial blush grade accompanies to higher sudden death risk scores of hypertrophic cardiomyopathy - Akkus, Oguz; Kaplan, Mehmet; Duman, Fatma; Yalcin, Fatih (Annals of Medical Research, 2021)
Aim: Hypertrophic cardiomyopathy (HCM) is predominantly inherited as an autosomal dominant disease. The aim of our study was to evaluate angiographic microvascular flow and predictors of poor MBG in patients with HCM.Material and Methods: Patients with poor MBG (MBG 0/1, n=43), and patients with normal MBG (MBG 2/3, n=15) were included retrospectively.Results: Family history and left ventricular end-diastolic diameter were significantly higher in the poor MBG group (p = 0.025, p=0.021). Left atrium diameter and moderate to severe mitral regurgitation (MR) were significantly higher in the normal MBG group (p=0.034, p=0.002). Percentage of SCD risk was significantly higher in patients with poor MBG (p=0.014). Moderate and severe mitral regurgitation (odds ratio =0.013, p=0.004) and HCM-SCD risk score (odds ratio = 0,398, p=0.009) were found to be independent parameters for predicting poor myocardial blush grade. The cut-off value of HCM-SCD risk score obtained by ROC curve analysis was 3.10 for the prediction of poor myocardial blush grade (sensitivity: 76.2%, specificity: 76.7%). The area under the curve (AUC) was 0.712 (p=0.016).Conclusions: Our study results demonstrated the increased risk of sudden cardiac death accompanies poor myocardial blush grade in patients with HCM. If confirmed by further studies, poor MBG may convey SCD-HCM risk of higher rates.Keywords: Hypertrophic cardiomyopathy; microvascular disease; sudden cardiac death risk score.